Drift capacity and allowable axial load level of RC columns. (February 2023) - Aydemir, Cem; Eser Aydemir, Müberra; Arslan, Güray
Highlights: Drift ratio and lateral deformation capacities of RC columns are investigated. A new axial load limit is defined in terms of drift ratio and column slenderness. Experimental test procedure is applied for six RC cantilever columns. Abstract: In this study, a new model is developed to estimate lateral deformation capacity or drift ratio of RC columns. This new model is applicable to all columns having greater shear capacity than demand. With this simple method, a new upper limit for axial load level of columns concerning drift demand and column slenderness variation is suggested. The results of the proposed method are compared not only with the experimental results of sample columns produced for current study but also a comprehensive database test results in literature. It is found from the comparisons that, drift ratio and slenderness of columns are key parameters effective on axial load limit. Besides, the consistency of axial load limits obligated in TBEC2018 and Eurocode 8 exhibit a decrease tendency for increasing values of drift ratio and slenderness effect.